2018
DOI: 10.14338/ijpt-18-00020.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment Modalities for High-Energy Proton Irradiation: Exploiting Specific DNA Repair Dependencies

Abstract: DNA repair deficiencies and genome instability are common features and hallmarks of cancer and are ubiquitously found in the full spectrum of malignant diseases. Heritable DNA repair deficiencies, for example, due to BRCA1 and BRCA2 mutations, and subsequent loss of heterozygosity in mammary, ovarian, and prostate carcinoma, are risk factors for the early development of cancer. Despite their detrimental role in tumorigenesis, these deficiencies also provide novel opportunities for treatment options. Current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…12,21,22 Although in vitro experiments suggest that proton therapy typically yields more DNA damage for the same dose relative to photons, there is no concrete evidence to suggest that biochemical control for prostate cancer is superior with PBT. 8,9 There is, however, a dosimetric advantage with respect to volumetric dose delivered to the bladder and rectum with PBT compared to photon-based EBRT. Therefore, the more likely advantage of PBT to be realized in future clinical trials lies with the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,21,22 Although in vitro experiments suggest that proton therapy typically yields more DNA damage for the same dose relative to photons, there is no concrete evidence to suggest that biochemical control for prostate cancer is superior with PBT. 8,9 There is, however, a dosimetric advantage with respect to volumetric dose delivered to the bladder and rectum with PBT compared to photon-based EBRT. Therefore, the more likely advantage of PBT to be realized in future clinical trials lies with the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Furthermore, preclinical studies have demonstrated higher relative biologic effectiveness (RBE) and more complex DNA damage for proton therapy compared with photon therapy. 7,8 Thus, compared to photon-based radiation, proton therapy might result in enhanced disease control and also fewer side effects in patients with high-risk prostate cancer. Despite these theoretical advantages, the use of proton therapy for prostate cancer remains a controversial topic due to its relatively high costs and lack of level 1 evidence to demonstrate that the dosimetric advantages of proton therapy translate to clinical benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, proton therapy produces greater complexity of DNA damage which requires different mechanisms for DNA repair. This may lead to enhanced disease control compared with photon‐based therapy . In addition, the gene expression responses suggest that protons may result in greater downregulation of certain genes that could impact metastases …”
Section: Opening Statementsmentioning
confidence: 99%